Asymmetric localization of natural antisense RNA of neuropeptide sensorin in Aplysia sensory neurons during aging and activity - Kadakkuzha, Beena M.; Liu, Xin-An; Narvaez, Maria; Kaye, Alexandra; Akhmedov, Komolitdin; Puthanveettil, Sathyanarayanan V. (Frontiers in Genetics, 2014)
Despite the advances in our understanding of transcriptome, regulation and function of its non-coding components continue to be poorly understood. Here we searched for natural antisense transcript for sensorin (NAT-SRN), a neuropeptide expressed in the presynaptic sensory neurons of gill-withdrawal reflex of the marine snail Aplysia californica. Sensorin (SRN) has a key role in learning and long-term memory storage in Aplysia. We have now identified NAT-SRN in the central nervous system (CNS) and have confirmed its expression by northern blotting and fluorescent RNA in situ hybridization. Quantitative analysis of NAT-SRN in micro-dissected cell bodies and processes of sensory neurons suggest that NAT-SRN is present in the distal neuronal processes along with sense transcripts. Importantly, aging is associated with reduction in levels of NAT-SRN in sensory neuron processes. Furthermore, we find that forskolin, an activator of CREB signaling, differentially alters the distribution of SRN and NAT-SRN. These studies reveal novel insights into physiological regulation of natural antisense RNAs.